Latin American and Caribbean Sex Workers: Gains and challenges in the movement - Cabezas, Amalia L. (Anti-Trafficking Review, 2019)
This article challenges the notion that the organised sex worker movement originated in the Global North. Beginning in Havana, Cuba at the end of the nineteenth century, sex workers in the Latin America and Caribbean (LAC) region have been organising for recognition and labour rights. This article focuses on some of the movement’s advances, such as the election of a sex worker to public office in the Dominican Republic, the system where Nicaraguan sex workers act as court-appointed judicial facilitators, the networks of sex worker organisations throughout the region, and cutting-edge media strategies used to claim social and labour rights. Sex workers are using novel strategies designed to disrupt the hegemonic social order; contest the inequalities, discrimination, and injustices experienced by women in the sex trade; provoke critical reflection; and raise the visibility of sex work advocacy. New challenges to the movement include the abolitionist movement, the conflation of all forms of sex work with human trafficking, and practices that seek to ‘rescue’ consenting adults from the sex trade.